Queer pedagogy in sex education - Drazenovich, George (Canadian Journal of Education/Revue canadienne de l'éducation, 2015)
While increased visibility of gay, lesbian, transgendered, and queer people in public settings, including schools, is certainly freeing for many students, critical questions concerning whether popular media depictions of LGBTQ identities serve to liberate students, or instead facilitate subtle strategies of containment and ghettoizing, are being raised. The present article argues that as a sex education strategy, the essentializing of sexual identity within sex education should be supplanted by more constructivist approaches; ones that allow for maximum individuation and self-expression. Rather than embracing particular labels and the commodification that sometimes flows from them in the popular media landscape, queer-positive sex educators might consider adopting some methods associated with spiritual pedagogy to assist students in rethinking questions of sexuality and creating new possibilities for identities and creative self-expression.